Scanning protocol optimisation for dual-energy computed tomography angiography in peripheral artery stenting - Almutairi, Abdulrahman Marzouq (Curtin University, 2016)
In this thesis, a novel approach has been proposed to evaluate the optimal scanning protocol for dual energy computed tomography angiography in peripheral arterial stents. This new approach includes evaluation of different protocols and image reconstructions at different energy level, development of the optimal protocol based on lowest radiation dose and acceptable image quality. Furthermore, an optimal contrast medium protocol has been identified in imaging peripheral arterial disease.